Evidence for a major missing source in the global chloromethane budget from stable carbon isotopes - Bahlmann, Enno; Keppler, Frank; Greule, Markus; Schöler, Heinz Friedrich (Atmospheric chemistry and physics, 2019)
Chloromethane (CH3Cl) is the most important natural input of reactive chlorine to the stratosphere, contributing about 16 % to stratospheric ozone depletion. Due to the phase-out of anthropogenic emissions of chlorofluorocarbons, CH3Cl will largely control future levels of stratospheric chlorine. The tropical rainforest is commonly assumed to be the strongest single CH3Cl source, contributing over half of the global annual emissions of about 4000 to 5000 Gg (1 Gg = 109 g). This source shows a characteristic carbon isotope fingerprint, making isotopic investigations a promising tool for improving its atmospheric budget. Applying carbon isotopes to better constrain the atmospheric budget of CH3Cl requires sound information on the kinetic isotope effects for the main sink processes: the reaction with OH and Cl in the troposphere. We conducted photochemical CH3Cl degradation experiments in a 3500 dm3 smog chamber to determine the carbon isotope effect (ε=k13C/k12C−1) for the reaction of CH3Cl with OH and Cl. For the reaction of CH3Cl with OH, we determined an ε value of (−11.2±0.8) ‰ (n=3) and for the reaction with Cl we found an ε value of (−10.2±0.5) ‰ (n=1), which is 5 to 6 times smaller than previously reported. Our smaller isotope effects are strongly supported by the lack of any significant seasonal covariation in previously reported tropospheric δ13C(CH3Cl) values with the OH-driven seasonal cycle in tropospheric mixing ratios. Applying these new values for the carbon isotope effect to the global CH3Cl budget using a simple two hemispheric box model, we derive a tropical rainforest CH3Cl source of (670±200) Gg a−1, which is considerably smaller than previous estimates. A revision of previous bottom-up estimates, using above-ground biomass instead of rainforest area, strongly supports this lower estimate. Finally, our results suggest a large unknown CH3Cl source of (1530±200) Gg a−1.
Gesehen am 31.07.2019